Hubungan Keterampilan Berpikir Tingkat Tinggi dan Kompetensi Literasi Sains Siswa SMA Negeri di Kabupaten Bulukumba - Reski, Fiska Indah; Daud, Firdaus; Taiyeb, A. Mushawwir; Pallenari, Muhiddin; Hiola, Siti Fatmah (Universitas Negeri Jakarta, 2024)
Various studies show that the scientific literacy of Indonesian students is still in a very low category, based on a review of the literature several factors are thought to be involved, namely related to the thinking ability of students who have not reached higher cognitive abilities in this case higher order thinking skills. So, this study aims to determine the relationship between higher order thinking skills and scientific literacy in public high school students in Bulukumba Regency, this research is a correlational type with a quantitative approach. The population in this study were all XII grade students at public high schools in Bulukumba Regency. The samples in this study were XII grade students at SMAN A, SMAN B, SMAN C, SMAN D, SMAN E, SMAN F, SMAN G, and SMAN H. Data collection techniques in this study used multiple choice tests that tested the C4-C6 level and scientific literacy tests tested in the PISA Program. Data analysis in this study was conducted using simple correlation test with Product Moment correlation method. The results showed that there is a relationship between higher order thinking skills and scientific literacy of high school students in Bulukumba Regency. This is based on the results of the analysis obtained showing that the significance value of learning is smaller than 0.05, namely (0.001 <0.05).